MANAJEMEN SUMBER DAYA MANUSIA (SDM) GURU TK DALAM PERSPEKTIF ADMINISTRASI PENDIDIKAN: STUDI LITERATUR - Dewi Tsalitsul Hamidah; Lia Mulyanengsih; Suklani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the concept of Human Resources (HR) management for Kindergarten (TK) teachers from an educational administration perspective and to identify strategies for strengthening HR quality based on a review of the latest literature. The method used is a literature study, analyzing journal articles, books, and official reports published between 2019 and 2024. The research results indicate that the HR management for Kindergarten teachers encompasses the processes of recruitment, selection, placement, professional development, performance appraisal, and welfare improvement. The biggest challenges include uneven teacher competence, minimal training, and weak academic supervision. This research recommends HR improvement strategies through continuous training, constructive academic supervision, objective performance appraisal, and strengthening teacher welfare.